A single gestational weight gain recommendation is possible for all classes of pregnant women with obesity. Issue 1 (January 2020) - Salmon, Charleen; Sauve, Reginald S.; LeJour, Caroline; Fenton, Tanis; Metcalfe, Amy
Abstract: Objectives: Obesity is a known risk factor for adverse pregnancy outcomes; however, appropriate gestational weight gain (GWG) may mitigate these risks. We investigated whether the singular 2009 Institute of Medicine (IOM) GWG guidelines were appropriate for all women with obesity, or whether separate recommendations were needed by class. Methods: This cross-sectional study of pregnant women with obesity used 2014 U.S. birth certificate data (N=646, 642) and included only term pregnancies. Adjusted log-binomial regression models examined the relative risk of adverse maternal, obstetric, and neonatal outcomes for pregnant women with class I–III obesity who: lost weight during pregnancy, gained below IOM guidelines, or gained above IOM guidelines, compared to women who gained within IOM guidelines. Results: Most women (55.1; 95% CI: 55.0-55.3) gained above IOM guidelines. As BMI severity increased, significantly fewer women had excessive GWG (Class I: 61.6%, 95% CI: 61.4-61.7; II: 50.7%, 95% CI: 50.4-50.9; III: 41.1%, 95% CI: 40.8-41.4). All classes of women with obesity who lost weight during pregnancy or gained below had a significantly decreased risk for caesarean delivery (RR (95% CI) class I: 0.92 (0.90-0.94); II: 0.91 (0.89-0.93); III: 0.92 (0.90-0.93)) and large-for-gestational age (LGA) births (class I: 0.80 (0.77-0.83); II: 0.76 (0.73-0.78); III: 0.73 (0.70-0.75)), but significantly increased risk of small-for-gestational age (SGA) births (class I: 1.34 (1.26-1.43); II: 1.38 (1.28-1.49); III: 1.35 (1.24-1.46)). Conclusion: The observed pattern of association was the same for all obese classes, hence evidence supports a possible singular GWG recommendation for all women with obesity, regardless of class.